Red Hat Certified System Administrator (RHCSA) : complete video course - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2015)
Red Hat Certified System Administrator (RHCSA) Complete Video Course is an engaging self-paced video training solution that provides learners with over 16 hours of personal, visual instruction from an expert trainer with over 20 years of practical Linux teaching experience. Through the use of topic-focused instructional videos you will gain an in-depth understanding of the Red Hat Certified Administrator (RHCSA) exam as well as a deeper understanding of Red Hat Enterprise Linux so you master the key foundational principles of systems administration. Included with the product are dynamic and interactive hands-on exercises and quizzes so you can test your knowledge while you study. The course includes 100% coverage of exam objectives, hands-on exercises included with each lesson so you can practice what you learned in a real CLI environment.